Monopolistic Competition, Resource Allocation and the Effects of Industrial Policy - Torbjørn Hægeland (Statistics Norway, Research Department, 1996)
An indicator of allocation effects of industrial policy is derived from a theoretical framework of monopolistic competition. The indicator gives a qualitative picture of how industrial policy affects industry structure and resource allocation, it identifies the policy measures that work as industry assistance under various assumptions about underlying parameters, and it allows a consistent comparison of the assistance effects of different measures. Indicator calculations of industrial policy represent an efficient alternative to numerical general equilibrium analyses, especially in international comparisons. Illustrative indicator calculations of Norwegian industrial policy are presented.
Keywords: F13; H25; L52; 330; Industry assistance; allocation effects; monopolistic competition; Norway.